2012
DOI: 10.1080/17470218.2012.656668
|View full text |Cite
|
Sign up to set email alerts
|

Bound context features are integrated at encoding

Abstract: In the present research, we tested the predictions of different accounts of context binding in "remember" judgements. Context binding, defined as the stochastically dependent retrieval of two different context features, has previously been suggested to be due to mechanisms operating at retrieval either by cueing among context features (Meiser & Bröder, 2002) or by cueing between item and context features (Starns & Hicks, 2008). These accounts, however, do not make specific assumptions regarding the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 41 publications
(85 reference statements)
2
34
2
Order By: Relevance
“…This prediction awaits further investigation. Regardless, the present results add to the evidence that direct context-context binding is not a necessary prerequisite of stochastic dependence (e.g., Boywitt & Meiser, 2012). There is no doubt that crossdimension cuing is elusive as an empirical phenomenon, whereas stochastic dependence is almost always observed.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…This prediction awaits further investigation. Regardless, the present results add to the evidence that direct context-context binding is not a necessary prerequisite of stochastic dependence (e.g., Boywitt & Meiser, 2012). There is no doubt that crossdimension cuing is elusive as an empirical phenomenon, whereas stochastic dependence is almost always observed.…”
Section: Discussionmentioning
confidence: 48%
“…An important finding in these paradigms is that the probability of correctly retrieving one source attribute is often dependent on correctly retrieving the other. This phenomenon was dubbed stochastic dependence by Meiser and Bröder. Theoretically, stochastic dependence has been interpreted as indicating the successful binding of item to source information but also of source to source information, sometimes referred to as context-context binding (Boywitt & Meiser, 2012), or as the successful creation of an episodic engram of highly integrated, interdependent elements (e.g., Horner & Burgess, 2013, 2014. Other studies have reinforced this interpretation.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Their use of the Remember/Know distinction was done to emphasize cases in which retrieval was supported by a strong sense of episodic recollection versus a more generalized sense of episodic familiarity (Gardiner, 1988;Rajaram, 1993;Tulving, 1985). Their subsequent work has emphasized this special condition of stochastic dependence being associated with recollection (e.g., Meiser, Sattler, & Weiber, 2008) and that this relationship with recollection has boundary conditions (e.g., Boywitt & Meiser, 2012a;Meiser & Sattler, 2007). For example, Boywitt and Meiser (2012a) demonstrated that stochastic dependence in the context of recollection follows only after encoding of the two source dimensions occurs close in time.…”
Section: A Renewed Focus On Multidimensional Source Memory Retrievalmentioning
confidence: 98%